Trichogramma spp. (Hymenoptera: trichogrammatidae) como agente de controle biológico de Erinnyis ello (Lepidoptera: sphingidae) - Carvalho , Leidiane Coelho (2020)
Biological control is an important alternative in the management of pest insects in the cassava crop. The parasitoids of eggs belonging to the genus Trichogramma (Hymenoptera: Trichogrammatidae) have a high potential for controlling the cassava mandarin tree, Erinnyis ello (Lepidoptera: Sphingidae). However, although they are important, there is little work to assess the potential of these parasitoids for their interactions and population dynamics, as well as fluctuation in the agroecosystem. In this sense, this work aimed to evaluate the population fluctuation of E. ello and its egg parasitoids collected in areas of commercial production of cassava and identifies lós, in addition to establishing the reproductive potential through biology studies and life table of fertility of T. manicobai and T. marandobai in E. ello eggs under laboratory conditions. In order to contemplate these objectives, the following tests were carried out: survey of the fluctuation of E. ello and its egg parasitoids carried out through collections of pest eggs; Identification of parasitoid species that occur in the area; biology of T. marandobai and T. manicobai in E. ello eggs. The occurrence of E. ello is verified at the beginning of the rainy season and the increase in temperature. The parasitoids of the genus Trichogramma have a high incidence in the analyzed areas. Since, the increase in parasitism followed that of the plague. Among the species that occur, three described and one species not described have been identified, namely, T. marandobai, T. manicobai, T. pretiosum and T. aff. marandobai, the species that predominates in the analyzed crops was T. marandobai. The evaluation of the biological parameters carried out with T. marandobai and T. manicobai indicate that both contribute in an important way to the natural biological control of E. ello.